Direct and indirect effects of agility, foot–eye coordination, and balance on football school players' dribbling performance - Syafiril Risman; Kamal Firdaus; Ridho Bahtra; Aldo Naza Putra (Global Econedu, 2026)
This study aimed to examine the direct and indirect effects of agility, foot–eye coordination, and balance on the dribbling performance of youth football players. A quantitative causal-comparative design was employed involving 27 players selected through purposive sampling from a population of 60 players at SSB Duri Galaxy, Bengkalis Regency. Agility, foot–eye coordination, balance, and dribbling performance were assessed using the Illinois Agility Run, Mitchell Soccer Test, Modified Bass Test of Dynamic Balance, and a standardized soccer dribbling test, respectively. Data were analyzed using path analysis at a significance level of α = 0.05. Agility demonstrated the strongest direct effect on dribbling performance (β = −0.934, p = .033), whereas balance showed a significant positive effect (β = 0.091, p = .001). Foot–eye coordination exhibited a positive but non-significant direct effect (β = 0.292, p = .073). Balance partially mediated the relationships between agility, foot–eye coordination, and dribbling performance. The proposed structural model explained 98.40% of the variance in dribbling performance (R² = .984). Agility is the primary determinant of dribbling performance, while balance strengthens the contribution of other physical capacities. Integrating agility, balance, and coordination into football-specific training may enhance dribbling performance among youth players.